Performance analysis on the influent of front tyres movement to the steering wheel system for steady and ride road conditions - Engku Izyan Munirah, Engku Afandi (2010)
This thesis concerns with the experimental analysis of the influent of front tyre movement to the steering system. The objective of this thesis is to analyse the relationship between steering wheel and tyres direction and also with speed while cornering for steady and ride road condition. The thesis describes the method to collect the on road performance data between steering wheel and tyre movement. Two different driving maneuver had been evaluate for this study purpose which are steady state cornering with constant radius and zigzag cone test. The test is perform in Universiti Malaysia PAHANG (UMP) and the data used for the analysis is obtained by using UMP Test Car which has been installed with wheel steering sensor and DEWESOFT software for data acquisition purpose. The post processing method was performed by using FlexPro and Microsoft Office Excel. The post processing method in FlexPro to determine the steering and wheel steer angle is being done by using FPScript function. The results of analysis were represented in spline curve graph of steering angle and wheel steer angle versus time. Comparisons between steering angle and wheel steer angle profile are made. The post processing method in Microsoft Office Excel is to determine the graph of steering angle versus tire direction and also steering angle versus speed. From the graph represented, some discussions are made to analyse each relationships. Comparisons between all the tests are made in achieving the conclusion. It has been observed that the vehicle is in understeer condition in all tests. The result concluded that the understeer condition is dependant on the slip angles and forces acting on the tires.